(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: The aim of this study was to evaluate level of drug resistance in Directly Observed Treatment, short course (DOTS) CAT-II failure Pulmonary tuberculosis patients admitted for retreatment according to Indian Revised National Tuberculosis Control Programme (RNTCP). Methodology: From January 2006 to December 2008 sputum samples were collected from all patients of DOTS CAT-II failure and transported to laboratory for Mycobacterium tuberculosis culture and drug susceptibility testing (DST). Category II failure pulmonary TB includes those patients who remained sputum positive after 5 months of CAT- II TB treatment. AFB culture was done on Lowan stein Jenson slopes (Solid culture), at Choithram hospital and research center which is RNTCP accredited laboratory. Results: DST results were available for 148 sputum smear positive DOTS CAT-II failure patients. Mean age of the patients were 33.96 years (range 15-65 years), male to female ratio was 1.79:1. Of the 148 patients, 50(33.78%) had Multidrug-resistant tuberculosis (MDR-TB) and 11(7.43%) had extensively drug-resistant tuberculosis XDR-TB. Out of 148 patients, 80(54.05%) had treatment after default and 68(45.94%) had treatment failure. The prevalence of MDR-TB and XDR-TB among category-II failure pulmonary tuberculosis patients was 33.7 and 7.43 per cent. Conclusion: The prevalence of MDR-TB strains was dramatically high among patients with pulmonary tuberculosis who failed category II therapy. Capacity of drug sensitivity testing is essential for continuous monitoring of drug resistance trends, in order to assess the effi cacy of current programme and epidemiological surveillance for planning. DOI: http://dx.doi.org/10.3126/saarctb.v8i2.5894 SAARCTB 2011; 8(2): 6-10